1981
DOI: 10.1111/j.1471-4159.1981.tb02378.x
|View full text |Cite
|
Sign up to set email alerts
|

δ‐Aminolaevulinic Acid Uptake, Toxicity, and Effect on [14C]γ‐Aminobutyric Acid Uptake into Neurons and Glia in Culture

Abstract: delta-Aminolaevulinic acid (ALA) uptake into neurons and glia in primary culture as well as ALA toxicity and its effects on gamma-aminobutyric acid (GABA) uptake were examined. [4-14C]ALA uptake into neurons and glia was nonsaturable, partially Na+- and temperature-dependent, and appeared to comprise mainly diffusion into the cell. 2,4-Dinitrophenol caused some inhibition of [4-14C]ALA uptake whereas ouabain, KCN, or amino acids at 1 mM concentration were without effect. ALA (1 mM) caused a slight inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Indirect mechanisms have also been postulated (Opler et al, 2004), including renal damage (Loghman-Adham, 1997), effects on transthyreitin secretion in the choroid plexus (Zheng et al, 1999), and interactions with nutrient absorption. It is also possible, as noted previously (Opler et al, 2004), that d-ALA could increase schizophrenia risk through neurotoxic effects on GABA neurotransmission (Percy et al, 1981). …”
Section: Risk Factor Studies Of Schizophreniamentioning
confidence: 66%
“…Indirect mechanisms have also been postulated (Opler et al, 2004), including renal damage (Loghman-Adham, 1997), effects on transthyreitin secretion in the choroid plexus (Zheng et al, 1999), and interactions with nutrient absorption. It is also possible, as noted previously (Opler et al, 2004), that d-ALA could increase schizophrenia risk through neurotoxic effects on GABA neurotransmission (Percy et al, 1981). …”
Section: Risk Factor Studies Of Schizophreniamentioning
confidence: 66%
“…Previously, a number of in vitro and in vivo studies have demonstrated the neurotoxicity of ALA mediated by effects on the GABAergic system [ 36 , 37 , 38 ]. However, this involvement was not entirely clear since some studies found slight and questionable effects [ 39 , 40 ], while other studies showed effects only at high concentrations of ALA [ 41 , 42 ], which would not normally be found in CNS diseases [ 36 ]. Despite the fact that ALA is an analogue to the neurotransmitter γ-aminobutyric acid (GABA), Emanueli et al .…”
Section: Discussionmentioning
confidence: 99%
“…These diseases are accompanied by a variety of neuropsychiatric symptoms (Brennan and Cantrill, 1979), and it has been suggested that these symptoms arise from the accumulation of the porphyrin precursors 5‐ALA and/or porphobilinogen (Yeung et al, 1987). 5‐ALA may be directly neurotoxic (Percy et al, 1981 ; Russell et al, 1983), and it may modulate CNS signal transduction by being an agonist for presynaptic GABA autoreceptors (Brennan and Cantrill, 1979). 5‐ALA has also been used clinically to delineate malignant gliomas (Stummer et al, 1998 c ).…”
mentioning
confidence: 99%